PFRET Measurements Using Sensitized Emission Methods in Observation of Calcium Changes in Oocytes - Nathania Nanasari; Djoko Herry Santjojo; Chomsin Sulistiya Widodo; Hari Soepriandono (Natural B, Journal of Health and Environmental Sciences, 2014)
Fluorescence Resonance Energy Transfer (FRET) is a process of non-radiative energy transfer from donor molecule to an acceptor. We expect to know the quantitative FRET measurements in immature and mature goat oocyte with the presence of calcium. FRET was detected using a laser scanning confocal microscope. We assume that calcium as a donor and fluo-3 as an acceptor. The methods of sensitized emission have been used for quantitative FRET measurement. We also describe the precision FRET (PFRET) data analysis. The value of PFRET describe the presence of calsium in immature and mature oocytes. For these immature and mature oocytes, the results of PFRET are 622,5 and 754,57 respectively. Mature oocyte has more calsium than immature oocyte.